Effect of extraction method on total phenolic content and antioxidant activity of Terminalia catappa (L.) leaves - Akmal, Tubagus; Julianti, Andi Ika; Tanjung, Yenni Puspita; Mutiara, Pipyt; Febriyanti, Sapitri (University Of Darussalam Gontor, 2024)
The potential for encountering free radicals poses a significant concern. Ketapang (Terminalia catappa L.) is a plant with antioxidant properties due to secondary metabolites, specifically phenolic compounds. The objective of this study was to determine the total phenolic content and antioxidant activity of ketapang leaves through the utilization of several extraction techniques. The extraction of Ketapang leaves is conducted using various methods, namely maceration, stirring-assisted extraction (SAE), ultrasound-assisted extraction (UAE), and microwave-assisted extraction (MAE) with 1:10 solid-solvent ratio. The total phenolic content of the Ketapang leaf extract was determined using the Folin-Ciocalteu technique and quantified using a UV-Visible spectrophotometer set at a wavelength of 782nm. Meanwhile, antioxidant activity measurements were carried out using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method and measured at a wavelength of 516nm. The study investigated the total phenolic content and antioxidant activity of Ketapang leaf extract using the maceration method of stirring-assisted extraction (SAE), ultrasound-assisted extraction (UAE), and microwave-assisted extraction (MAE), respectively, were 68.495%+2.891, 75.709%+0.106, 84.269%+0.159, and 65.065%+3.965 mgGAE/g and 20.891, 17.569, 15.427, and 21.353 µg/mL. The findings of this study indicate that the ultrasound-assisted extraction technique exhibits the greatest overall phenolic content and antioxidant activity. Keywords: antioxidant, Terminalia catappa, total phenolic content, ultrasound-assisted extraction